2007
DOI: 10.1037/0021-9010.92.5.1456
|View full text |Cite
|
Sign up to set email alerts
|

Work characteristics, musculoskeletal disorders, and the mediating role of psychological strain: A study of call center employees.

Abstract: The demands of the modern office are thought to contribute to the development of musculoskeletal disorders. For upper body and lower back disorders, these effects are hypothesized to be mediated by psychological strain. A study of 936 employees from 22 call centers supports this hypothesis. Using logistic regression and structural equation modeling, the authors found that the relationship of workload to upper body and lower back musculoskeletal disorders was largely accounted for by job-related strain. This me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
69
0
8

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(81 citation statements)
references
References 60 publications
4
69
0
8
Order By: Relevance
“…Numerous studies have examined productivity, workrelated stress, musculoskeletal disorders and caller quality service issues in call-center workers [6][7][8][9][10][11][12][13][14] . For instance, Burton et al 12) indicated that productivity decreases as the health risks faced by call center operators increase.…”
mentioning
confidence: 99%
“…Numerous studies have examined productivity, workrelated stress, musculoskeletal disorders and caller quality service issues in call-center workers [6][7][8][9][10][11][12][13][14] . For instance, Burton et al 12) indicated that productivity decreases as the health risks faced by call center operators increase.…”
mentioning
confidence: 99%
“…De nombreuses recherches ont étudié les services à la clientèle en lien avec des éléments de la charge de travail et la santé (Sznelwar et al, 1999;Sprigg et al, 2007;Moller et al, 2008;Chouanière, Boini et Colin, 2011). On y atteste une exigence psychologique élevée, une faible latitude décisionnelle, une forte exigence émotionnelle en lien avec la confrontation avec les clients de toutes sortes et une dissonance émotionnelle, car les agents doivent toujours afficher des émotions positives.…”
Section: Résumé De L'articleunclassified
“…This body of work is said to be made up of the following: Danford, 1998;1999;Delbridge, 1998;Landsbergis et al, 1999;Lewchuk and Robertson, 1997;Mehri, 2006;Sprigg and Jackson, 2006;Sprigg et al, 2007;and Stewart et al, 2009. There are a number of things that need to be said about this.…”
mentioning
confidence: 99%
“…The first is to question the extent to which these books and articles together constitute a cohesive 'body' of work in the way that Carter et al claim. If we look at some of these works individually, we can note, for example, that Sprigg et al (2007) contains no mention at all of lean management. Delbridge's (1998) book is concerned with how employees work under Lean, but it is at least questionable whether it takes the line that Carter et al attribute to it (see Procter, 2001).…”
mentioning
confidence: 99%